Human Resource Management Challenges in the Hospitality Industry: Insights from Nepal - Shrestha, Surya Kiran (Nepalese Journal of Hospitality and Tourism Management, 2020)
Hospitality industry in Nepal is growing along with tourism industry, which is further supplemented by the rising entry of international chain of hotels. It has increased the demand for the efficient management of qualified human resources. However, there are also challenges at varying levels to manage human resources in this industry. Therefore, this paper explores human resource management (HRM) challenges in the hospitality industry. The data for this study was collected through in-depth semi-structured interviews of 20 HR directors/managers from the Nepalese five-star and four-star hotels who were chosen using a purposive sampling method to ensure that the participants have enough experience of managing human resources in hotels. The findings reveal both internal as well as external challenges faced by the Nepalese hospitality industry.